A Rare Complication Unveiled: Ostial Left Main Stenosis Post SAVR—A Case Report - Emmanuel Daniel MD; Mohammed El-Nayir MD; Thomas Dougan MD; Priyata Dutta MD; Paul Nona MD (Journal of Investigative Medicine High Impact Case Reports, 2025)
Iatrogenic coronary artery obstruction is one of many life-threatening complications associated with aortic valve replacement. Although very few cases of ostial coronary artery occlusion following cardiac surgery are reported, the consequences can be catastrophic due to increased risk of mortality. Due to the rarity, prompt investigation and early management are crucial to manage this catastrophic sequelae. We report a case in which a 61-year-old female presented with acute coronary syndrome 4 months after surgical aortic valve replacement and was found to have 99% left main ostial coronary artery occlusion.